Daya Terima Fudgy Brownies Substitusi Carob Powder - Karimah, Kamilia; Mahmudatussa’adah, Ai; Patriasih, Rita (Jurnal Sains Boga, 2024)
Chocolate is a popular product that is loved by the public. The high demand for chocolate is not in line with the decreasing production of chocolate due to climate change, resulting in the increasing price of chocolate. Chocolate is used in various pastry products such as fudgy brownies. Fudgy brownies are dense, moist and have a strong chocolate flavor and aroma. Carob powder can be an alternative to chocolate because it has sensory characteristics of taste and color similar to chocolate and a lower price. The purpose of this research is to increasing the use of carob powder as a substitute for chocolate in making fudgy brownies and the resulting public acceptance. This research uses the true experimental method through the stages of recipe analysis, product development, QDA (Quantitative Descriptive Analysis) test and acceptance test. The results obtained for the standard recipe formula for fudgy brownies with carob powder substitution, namely carob powder can replace 50% of the total chocolate powder used. The sensory characteristics of carob powder substituted fudgy brownies have a strong aroma and taste of chocolate with a blackish brown color. Acceptability results showed that fudgy brownies with carob powder substitution were acceptable to the public.